Kasedesede as a Culturally Responsive Medium for Mathematics Learning: Students’ Perceptions and Numeracy Outcomes - Rimayasi Rimayasi; Anisa Rizkayati; Eka Rosmitha Sari; Afriningsih Harjuniati; La Ode Arku; Wa Ode Siti Elma Sari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study aimed to analyze students’ perceptions of the Kasedesede traditional game as a medium for mathematics learning and to examine its relationship with numeracy performance. A quantitative descriptive design was employed with a saturated sample of 39 fifth-grade students in Baubau City, Southeast Sulawesi. Data were collected through a Likert-scale questionnaire consisting of six dimensions: engagement, enjoyment, mathematical understanding, literacy-numeracy, attitudes toward mathematics, and socio-educational benefits, together with a contextual numeracy test. Descriptive statistics, regression analysis, and Support Vector Machine with heatmap visualization were used for analysis. The results indicated that students expressed highly positive perceptions of Kasedesede-based lessons, with enjoyment and engagement emerging as the most influential dimensions. Regression results showed that perceptions significantly predicted numeracy outcomes, accounting for 26.2% of the variance. Further analysis confirmed that enjoyment, literacy-numeracy, and socio-educational benefits played a dominant role in shaping performance. These findings suggest that integrating traditional games into mathematics lessons not only supports conceptual understanding but also fosters motivation, positive attitudes, and collaborative learning. The study contributes to the body of knowledge on ethnomathematics and culturally responsive pedagogy, highlighting the potential of traditional games as innovative and humanistic strategies for improving literacy and numeracy in primary education.